Effects of E-Marketing and Social Media Marketing on E-commerce Shopping Decisions - Donni Juni Priansa; Bethani Suryawardani (Jurnal Manajemen Indonesia, 2020)
This research analyzes how marketing through electronic media, marketing through social media, and purchasing decisions on e-commerce sites; testing whether marketing through electronic media has a positive effect on buy decisions at e-commerce sites; testing whether marketing through social media has a positive effect on buy decisions at e-commerce sites; and test whether marketing through electronic media and social media marketing has effect on buy decisions at e-commerce sites. The survey method was used in this study. The population of e-commerce consumer research in Bandung. The sample size used was 125 samples. Path analysis used to analyze data. Findings, marketing through electronic media, marketing through social media, and consumer decisions were in the high category. Marketing through electronic media has effect to buy decisions at 45.35%; Marketing through social media has effect to buy decisions at 35.73%. Marketing through electronic media and social media has effect to consumer decisions at 81.08%. Keywords: E-marketing; Social Media Marketing; Purchase Decision